Preventing the harmful effect on fauna at oil wells arrangement and operation - Potapov, Dmitry V.; Галиновский , Николай Геннадьевич; Averin, Viktor S.; Demidenko, Oleg M. (Journal of the Belarusian State University. Ecology, 2022)
The damage that is incurred to zoobiota by oil wells development and operation has been evaluated for Gomel region for the first time. This evaluation has been made based on the analysis of zoocenoses state under the conditions of ecosystems that are linked to oil exploration and production sites. Measures and practical recommendations have been also developed. They can reduce the damage incurred. It has been found out that development of an additional area facilitates the conservation of invertebrate animals species composition by edge effect formation. This area is up to 20 meters wide and planted with grass and shrubs. The absence of such a buffer zone leads to ingress of sand to a forest ecosystem, changes its hydrological conditions, which factors into trees shrinkage and increase of secondary insects number. It has also been revealed that the equipment of oil wells in grassland ecosystems brings about changes in species composition of invertebrate communities. The above-mentioned equipment is associated with natural thatch removal as well as with cutting down trees and shrubs, and injection of sand here to develop bunding zone and setback (buffer) area. Similar anthropogenic transformation of grassland ecosystems is accompanied by an increase of the number of invertebrate animals inhabiting vast sand spaces and a decrease in the proportion of species preferring grassy habitats. As a result of research, it has been shown that it makes sense to preserve the soil layer removed at technological works for further soil reclamation of the transformed ecosystem. It has been detected that the Coleoptera number has increased within the site in the setback (buffer) area of oil wells. Grass mixture of red and sheep's fescue, meadow grass, and perennial ryegrass were sowed on this site and the complex nitrogen-phosphate fertilizer was added. Moreover, species abundance inhabiting sand areas has been decreasing within seeds and the number and richness of meadowy species tending to areas of high projective grass cover have been increased. At the same, time there is an increase of Coleoptera number neat the outer edge of seeds as in the case with invertebrate animals. In our opinion, it can be explained by a particular border effect.
Keywords: zoobiota; oil production; oil wells operation; damage evaluation; practical recommendations